2018
DOI: 10.1038/s41598-018-28134-1
|View full text |Cite
|
Sign up to set email alerts
|

The Open Source GAITOR Suite for Rodent Gait Analysis

Abstract: Locomotive changes are often associated with disease or injury, and these changes can be quantified through gait analysis. Gait analysis has been applied to preclinical studies, providing quantitative behavioural assessment with a reasonable clinical analogue. However, available gait analysis technology for small animals is somewhat limited. Furthermore, technological and analytical challenges can limit the effectiveness of preclinical gait analysis. The Gait Analysis Instrumentation and Technology Optimized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…A walking arena was built for gait analysis as per guidance provided in the GAITOR Suite . Gait videos were recorded at 400 fps and approximately 1,350 μs of exposure time (PROMON U750; AOS Technologies, Baden‐Daettwil, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…A walking arena was built for gait analysis as per guidance provided in the GAITOR Suite . Gait videos were recorded at 400 fps and approximately 1,350 μs of exposure time (PROMON U750; AOS Technologies, Baden‐Daettwil, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Lewis rats are more often used as the subjects in critical nerve defect models over other alternative rodent strains due to minimal occurrence of autotomy behavior after an extended period post-transection of the sciatic nerve gap (18). This is supported by previous studies that have highlighted the physiological behavior changes in different rodent strains after induction of critical size nerve defects (19,20).While previous studies have reported normal kinematic data from these rat strains, there does not appear to be any literature that compares the normal gait pattern of Sprague Dawley rats to Lewis rats using a pressure mat system (21)(22)(23)(24). In this study we will be comparing gait parameters between Sprague Dawley and Lewis rats.…”
Section: Introductionmentioning
confidence: 62%
“…This was further confirmed when grouping the mean values of the limbs for each group, which showed statistically similar stride velocity and acceleration for each limb while normalized force and contact area values remained statistically different between forelimbs and hindlimbs. Previous studies have used rodents as a control group for normal gait motion and have described this gait pattern where the hindlimbs will support more of the rodent's weight compared to the forelimbs due to unequal distribution of the rodent's weight across its body frame from the front end to the back end (7,23). This also explains why the stance time variable has a large variance between the forelimbs and hindlimbs for both rodent groups, as the greater weight supported by the hindlimbs needs more time to stabilize and propel the body forward during normal gait motion.…”
Section: Discussionmentioning
confidence: 99%
“…associated hardware and open-source analysis software were used to acquire spatiotemporal gait data [17,23,24] (additional information available online 1 ). Briefly, the arena is an enclosed, Fig.…”
Section: Spatiotemporal Gait Testing a Custom-built Gait Arena Withmentioning
confidence: 99%
“…Additionally, a recent study evaluated gait changes due to elbow contracture in a murine model [22]; however, in this study animals were only evaluated at a single time point for a single gait parameter. In this study, spatiotemporal gait compensations were investigated longitudinally in our rat PTJC model using an open source, fully automated technique validated to detect rodent gait abnormalities with high sensitivity [23,24]. We hypothesized (1) the unilateral, persistent range of motion loss observed previously [7] would be manifested as an asymmetric gait with imbalanced duty factor and reduced grip strength when compared to uninjured controls, and (2) metrics of gait and grip strength would partially recover over time but not reach levels of control animals.…”
Section: Introductionmentioning
confidence: 99%